Materials Used in Splinting and Splint Types - Aslan, Cansu; Kaya, Filiz Acun (Van Yuzuncu Yıl University, 2022)
The importance of splints in terms of periodontal treatment has been the subject of discussion in recent years. And splints may not always be indicated. It should be known that splint treatment does not completely eliminate the periodontal problem, but provides a partial recovery. The decision of splinting should be considered and made by keeping the patient under follow-up after periodontal treatments. Indications for splinting are generally limited to controlling post-traumatic mobility and making functions such as chewing and biting more comfortable for the patient. However, satisfactory treatment results are obtained after the correct indication and especially with splint types developed recently. Splinting treatment is a valuable treatment method, as it reduces the mobility and ensures both the protection of the health of periodontal soft tissues and the prevention of resorptions caused by mobility in the bone.

Periodontal tedavi açısından splintlerin önemi son yıllarda tartışma konusu olmuştur.Ve splintler her zaman endike olmayabilirler. Splint tedavisinin periodontal problemi tam anlamıyla gidermediği kısmen bir iyileşme sağladığı bilinmelidir. Splintleme kararı, yapılması gereken periodontal tedaviler sonrasında hasta takip altında tutularak du?şu?nu?lu?p verilmelidir. Splintleme endikasyonları genellikle travma sonrası oluşan mobiliteyi kontrol etmek, hastada çiğneme, ısırma gibi fonksiyonların daha konforlu hale gelmesini sağlamakla sınırlıdır. Ancak doğru endikasyon sonrası ve özellikle son dönemlerde geliştirilen splint çeşitleriyle tatmin edici tedavi sonuçları alınmaktadır. Splintleme tedavisi, mobilitenin azalmasını sağlayıp hem periodontal yumuşak dokuların sağlığının korunmasını hem de kemikteki mobiliteyle oluşan rezorbsiyonların önu?ne geçilmesini sağlandığından kıymetli bir tedavi yöntemidir
Splintlemede Kullanılan Materyaller Ve Splint Tipleri
Keywords: Periodontics; Periodontoloji